Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, dan Islamic Governance Score Terhadap Pengungkapan Islamic Social Reporting (Studi Empiris pada Bank Umum Syariah di Indonesia Tahun 2010-2012) - Rosiana, Rita; Arifin, Bustanul; Hamdani, Muhamad (Esensi: Jurnal Bisnis dan Manajemen, 2015)
Conventional social responsibility disclosure is measured by an index of global reporting initiative is limited to the material aspects of the course, while the Islamic social responsibility disclosure is not limited to the material aspect alone, but on the spiritual and moral aspects of the social reporting by Islamic index. Limitations of conventional social responsibility disclosure push this study to determine the factors that influence disclosure of social reporting on Islamic sharia banks in Indonesia.The study involved Islamic banks in Indonesia in 2010-2012. The research method used is content analysis are derived from annual reports or corporate websites Indonesian stock exchange in 2010-2012. Statistical program used was Statistical Package for Social Sciences SPSS 20.0 by using multiple linear regression analysis.The variables used in this study are firm size as measured by total assets, profitability as measured by return on assets, leverage as measured by debt to equity ratio and Islamic governance score as measured by the number, cross membership, educational background, and the reputation of the council supervisor sharia as the independent variable, and Islamic social reporting as the dependent variable. The results pointing to a company that size has a significant influence on the disclosure of Islamic social reporting, while the rest has no effect.DOI: 10.15408/ess.v5i1.2334